Going local: placing entrepreneurial microgeographies in a larger regional context. Issue 8 (13th September 2020) - Donegan, Mary; Lowe, Nichola
ABSTRACT: As cities seek to promote innovation,  they are increasingly investing in localised institutional entrepreneurial supports. Some institutions are hyperlocal, operating within distinct geographic sub-spaces and funnelling entrepreneurial ventures within spatially bounded microgeographies. In this paper, we focus on the University of North Carolina, where actors from the business school helped build a unique web of hyperlocal entrepreneurial supports that reinforced core educational and research missions but also culminated in proximate university business incubators. We examine how this programmatic changes correspond to a marked increase in entrepreneurial intensity as well as ageographic tightening of firms in and around the campus. Yet we also find evidence for an additional effect, namely an earlier launch of entrepreneurial firms based on less-tested technologies. The results speak to the power of institutional actors in shaping entrepreneurial activities while raising broader questions about the impact of university programming on regional industry and innovation.